Functionalized nitrogen-doped carbon dot-modified yolk-shell ZnFe2O4 nanospheres with highly efficient light harvesting and superior catalytic activity - Li, J.; Li, X.; Zeng, L.; Fan, S.; Zhang, M.; Sun, W.; Chen, X.; Tadé, M.; Liu, Shaomin (R S C Publications, 2019)
Volatile organic compounds (VOCs), as hazardous gaseous pollutants, have attracted much attention due to their potential threat to both human health and the environment. Accordingly, photocatalysis technology is seen as a promising technology to control low concentration VOCs due to its mild operation conditions, low energy consumption, and mineralization ability. However, there are some issues with photocatalysts, such as low light utility and fast photogenerated carrier recombination, which need to be addressed for practical applications. In this work, novel nitrogen-doped carbon dot (NCD)-modified ZnFe2O4 yolk-shell nanostructure photocatalysts were fabricated for the first time. The yolk-shell structure of ZnFe2O4 efficiently shortened the photogenerated carrier migration path and enhanced light scattering in its void, while the decorated NCDs accelerated the charge transfer from the bulk to the surface. A series of characterizations was conducted to investigate the crystal structure, elemental status, optical properties, and photocatalytic performance of the obtained composite photocatalysts. The NCD-modified ZnFe2O4 yolk-shell photocatalysts exhibited both a wide spectral absorbance and low carrier recombination, resulting in high photocatalytic activity and degradation ability towards gaseous o-dichlorobenzene. Density functional theory (DFT) calculations further revealed that the NCDs effectively promoted charge transfer and weakened the recombination of photo-generated electron-hole pairs. Additionally, in situ Fourier transform infrared (FTIR) spectroscopy was performed to investigate the degradation path in the photocatalytic process, and an electron paramagnetic resonance (EPR) radical trapping experiment was conducted to unveil the reactive oxygen species involved in the system. Combining the results obtained, the synergistic effect in the enhancement of photocatalysis between NCDs and yolk-shell ZnFe2O4 was schematically proposed.